Awareness of Dystonic Posture in Patients With Cervical Dystonia - Ferrazzano, Gina; Berardelli, Isabella; Belvisi, Daniele; De Bartolo, Maria Ilenia; Di Vita, Antonella; Conte, Antonella; Fabbrini, Giovanni (Frontiers in Psychology, 2020)
Abstract Background: Cervical dystonia (CD) is a focal dystonia characterized by sensorimotor integration abnormalities and proprioceptive dysfunction. Since proprioception is essential for bodily awareness, we hypothesized that CD patients may have an impairment in dystonic posture awareness. More information on this issue could be useful to better understand whether dystonic posture affects bodily perception in CD and could help in the development of specific rehabilitation strategies based on proprioceptive input manipulation to restore bodily awareness. Objectives: The aim of our study was to investigate dystonic posture and head tremor awareness in CD patients by comparing evaluations performed by CD patients with those performed by a neurologist expert in movement disorders. Methods: We enrolled 25 CD patients. We investigated dystonic posture and head tremor awareness in CD patients using a standardized protocol in which patients were asked to describe the type of dystonic pattern, both while viewing standardized images of different CD subtypes (torticollis, laterocollis, anterocollis, and retrocollis) and after watching a video recording of their dystonic posture and head tremor. Results: We found that 72% of CD patients correctly recognized their dystonic posture when viewing standardized images, whereas 84% of CD patients were able to identify their dystonic pattern when watching a video recording of themselves. CD patients also displayed a preserved awareness of their head tremor. We did not find any associations between dystonic pattern awareness and clinical or demographic features. Conclusions: Contrary to our hypothesis, the majority of CD patients have a preserved awareness of their dystonic pattern and tremor.